Návrh uplatnění procesního řízení při navyšování produktivity práce - Kubíček, Filip (Vysoké učení technické v Brně. Fakulta podnikatelská, 2012)
Bakalárská práce je zamerená na zvýšení produktivity práce na daném zarízení v podniku DHD spol. s r.o., který se zabývá výrobou impregnovaného papíru a laminovaných desek. Na základe analýzy procesu na pracovišti jsou podány návrhy a možná opatrení vedoucí k minimalizaci casových ztrát, což znamená maximalizaci produktivity.

This bachelor thesis is aimed at increasing in labour productivity of given device of the company DHD Spol. s r.o. which is engaged in production of impregnated paper and laminated boards. On the basis of the results of process analysis there are given proposals and possible measurements which lead to minimalization of time losses which mean maximization of pruductivity.
The Project of Application the Procedural in Raising Labor Productivity
Keywords: Produktivita; výroba; zmetkovitost; proces; ergonomie; Productivity; production; waste; process; ergonomic